Differences of Micro-CT evaluation of the obturation sealing capability between thermoplastic carrier-based condensing techniques and lateral heat condensation techniques - Amida, Aya; Aripin, Dudi; Hayati, Ayu Trisna; Latief, Fourier Dzar Eljabbar; Djustiana, Nina; Cahyanto, Arief; Usri, Kosterman; Tjahajawati, Sri; Mariam, Marry Siti; Widyaputra, Sunardhi (Padjadjaran Journal of Dentistry, 2022)
ABSTRACT Introduction: Root canal filling is an important part of root canal treatment that aimed to seal the root canal system, to prevent bacterial penetration and their toxins into periradicular tissues and to provide favourable environment for periapical healing. Thermoplasticized technique were developed to produce filling with homogenous mass, to achieve optimal sealing ability and to increase the quality of root canal filling. The aim of this study is to analyzed differences of Micro-Computed Tomography (Micro-CT) evaluation of the obturation sealing capability between thermoplastic carrier-based condensing techniques and lateral heat condensation techniques. Methods: This study was conducted under an in-vitro quasi experimental methode to 36 specimens of maxillaris centralis incisivus which were divided to 3 groups, (A) thermoplasticized carrier-based technique (GuttaCore System), (B) warm lateral condensation technique (heat carrier SystemB), (C) cold lateral condensation as control group. Sealing ability is evaluated based on the measurement results of volume percentages of filling material and sealer, volume of void, and surface density, that which was calculated from the 3D volumetric image of Micro-CT device. Data were statistically analysed using Analisis of Variance (ANOVA) and t-test. Result: The result showed significant difference of percentage filling material and sealer volume in apical third (p<0.05), whereas there were no significant differences of void volume in apical third, middle third, coronal third or along the canal (p>0.05). Conclusion: Thermoplastized carrier-based technique is not better than warm lateral technique.Keywords: sealing ability; root canal filling; thermoplasticized carrier-based technique; warm lateral technique.